Saddle point approximation to higher order - Fabiano, Nicola; Mirkov, Nikola (Vojnotehnički glasnik / Military Technical Courier, 2022)
Introduction/purpose: Saddle point approximation has been considered in the paper.Methods: The saddle point method is used in several different fields of mathematics and physics. Several terms of the expansion for the factorial function have been explicitely computed.Results: The integrals estimated in this way have values close to the exact one.Conclusions: Higher order corrections are not negligible even when requiring moderate levels of precision.
Keywords: saddle point approximation; Stirling’s formula; Quantum Field Theory